Public Sector Debt Statistics : Guide for Compilers and Users. (Manuals and Guides, 2013)
The global financial crisis of recent years and the associated large fiscal deficits and debt levels that have impacted many countries underscores the importance of reliable and timely government statistics and, more broadly, public sector debt as a critical element in countries fiscal and external sustainability. Public Sector Debt Statistics is the first international guide of its kind, and its primary objectives are to improve the quality and timeliness of key debt statistics and promote a convergence of recording practices to foster international comparability and as a reference for national compilers and users for compiling and disseminating these data. Like other statistical guides published by the IMF, this one was prepared in consultation with countries and international agencies, including the nine organizations of the Inter-Agency Task Force on Finance Statistics (TFFS). The guide's preparation was based on the broad range of experience of our institutions and benefitted from consultation with national compilers of government finance and public sector debt statistics. The guide's concepts are harmonized with those of the System of National Accounts (2008) and the Balance of Payments and International Investment Position Manual, Sixth Edition.